Faktor- Faktor Yang Mempengaruhi Keputusan Pembelian Konsumen di Virgin Cake & Bakery Tlogosari Semarang - Jong Stefanus; Dwi Hayu Agustini (Universitas Katolik Soegijapranata, Semarang, 2019)
This research aimed to know what factors and which one was the most effective in influencing the consumer purchasing decision in Virgin Cake Bakery at Tlogosari Semarang. The sample number of research using purposive sampling was 70 respondents. Analysis conducted was descriptive. Result of analysis showed that there 22 factors affecting consumer purchasing decision. The factors were grouped in 5 factors namely product, service, price, location and information source